Internet of Paint (IoP): Design, Challenges, Applications, and Future Directions - Lasantha Thakshila Wedage; Mehmet Can Vuran; Bernard Butler; Christos Argyropoulos; Sasitharan Balasubramaniam (IEEE Access)
The proliferation of nano-technology has enabled novel applications in various fields, including the potential for miniaturized terahertz (THz)-enabled devices. The extra-large bandwidth available in the THz spectrum can facilitate high-speed communication, even for transmission through lossy media. Culminating these capabilities, this paper introduces a new paradigm: Internet of Paint (IoP), transforming the 40,000-year-old concept of paint with extensive connectivity and sensing capabilities. IoP will enable seamless, massively parallel, and high-capacity communication and sensing capabilities, enabling innovative applications. IoP is expected to offer communication and sensing using nano-devices embedded in paint. In this paper, challenges towards the realization of IoP are discussed. Simulations indicate that THz signals in this stratified medium can form lateral waves that propagate along the Air-Paint interface and that relatively high channel capacity can be achieved by optimizing the transceiver locations, the paint thickness, and color. Addressing the challenges regarding nano-devices, nano-transceivers, materials, antennas, and power for IoP holds the potential to transform communication technologies and their seamless integration with living spaces.